Analisis Yuridis Pelaksanaan Corporate Social Responsibility (CSR) Pasca Pertambangan Indonesia - Nurmala, Sheila Adi; Utami, Ikawati (Universitas Batanghari Jambi, 2025)
The implementation of post-mining Social Responsibility of Corporations (CSR) in Indonesia has become a major concern along with increasing awareness of sustainability and Social Responsibility of Corporations. The mining sector does contribute significantly to the national economy, but it also has negative impacts on the environment and surrounding communities. This investigation uses a normative juridical approach by analyzing various regulations, including Regulation Point 40 per 2007 concerning Limited Liability Companies, Regulation Point 4 per 2009 in conjunction with Regulation Point 3 per 2020 concerning Mineral and Coal Mining, Regulation Point 25 per 2007 concerning Investment, Regulation Point 32 per 2009 concerning Environmental Protection and Management, and Government Regulation Poin 47 per 2012 and Government Regulation Poin 96 per 2021. This study is based on the concept of sustainable CSR (Triple Bottom Line) and the theory of corporate responsibility, which emphasizes the balance of economic, social, and environmental aspects. A case study of corruption at PT Timah Tbk serves as an illustration to assess the gap between legal norms and practice in the field. The analysis shows that despite fairly comprehensive regulations, the implementation of post-mining CSR still faces various obstacles, such as legal uncertainty, weak oversight, limited human resource capacity, small budgets, low community contributions, and the absence of strict sanctions for violators. Therefore, CSR management reform is needed through strengthening regulations, increasing supervisory capacity, transparency in fund use, and active community involvement. The government is expected to play a more active role as a regulator, facilitator, and supervisor so that post-mining CSR can be implemented effectively, sustainably, and equitably.